Genomic profiles of Pyricularia oryzae in Sub-Saharan Africa: exploring population differences and their evolutionary implications in the region - Onaga, Geoffrey; Suktrakul, Worrawit; Wanjiku, Margaret; Quibod, Ian Lorenzo; Domelevo Entfellner, Jean-Baka; Bigirimana, Joseph; Habarugira, Georges; Murori, Rosemary; Asea, Godfrey; Tella, Hamidatou Euridice; Amagnide, Gbenakpon Aubin G. Y.; Zenna, Negussie; et al. (Frontiers in Plant Science, 2025)
BackgroundRice blast, caused by Pyricularia oryzae (teleomorph: Magnaporthe oryzae), is one of the most economically damaging diseases affecting rice worldwide. While the evolutionary origins and genetic structures of Asian and European P. oryzae populations are relatively well characterized, African isolates remain underexplored. This knowledge gap impedes the development of informed management strategies for rice blast in the region. The present study was conducted to characterize the genetic origins, population structure, admixture, demographic history, and effector gene diversity of P. oryzae isolates in SSA, and to elucidate their evolutionary trajectories and implications for disease management.MethodsA total of 180 genome sequences (45 from SSA, 135 from other regions) were analyzed using population genomic approaches. Phylogeographic reconstructions, demographic modeling, and genome-wide association studies were performed to trace migration events, quantify genetic diversity, and identify candidate adaptation genes. Effector gene repertoires were also examined for diversity and selection signatures. ResultsOur findings provide new dates for the divergence of SSA populations from Asian populations. The introduction of P. oryzae into Africa occurred mainly from China in the late 19th century, initially in West Africa (WA; Mali and Burkina Faso), and subsequently in Uganda and Madagascar during the early 20th century, before extending to the wider African region, with subsequent repeated introductions. Tajima’s D and demographic modeling suggested complex population dynamics shaped by migration and asymmetric founder events, highlighting considerably shared genetic ancestry between Asia and East Africa (EA), in contrast with that between Asia and WA. Genome-wide association analysis identified a specific set of single nucleotide polymorphism markers, along with several candidate genes linked to adaptation. Effector analysis revealed that SSA isolates harbor fewer effectors and exhibit lower genetic diversity than Asian populations, with some effectors under positive selection, particularly in WA.DiscussionP. oryzae populations in SSA are shaped by historical introductions, founder events, and region-specific adaptation processes. While WA populations have diverged significantly from their Asian ancestors, gene flow within SSA connects regional populations, and effector gene diversity reflects both conserved virulence strategies and adaptation to local hosts. Overall, this study improves the existing knowledge on P. oryzae populations in SSA and underscore the need for integrated management strategies that consider both historical and contemporary pathogen dynamics in Africa.